(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2020)
The so-called “cinepanettone” has been one of the most typical genres of Italian popular cinema since 1983. Compiled soundtracks made up of the latest pop hits and commercial house music are unquestionably among the most prominent conventions defining such movies. The goal of the article is to examine how such music became typically associated with the “cinepanettone”, in relation with the wider context of popular music and media in 1980s and 1990s Italy; and (following O’Leary’s suggestions) to discuss the “phenomenology” of such repertoire, in order to criticize the notion of “cinepanettoni” music as the quintessential “bad music”.